LEKSIKON DALAM TRADISI PERKAWINAN MORUMBANDOLE PADA SUKU TOLAKI DI KECAMATAN WUA- WUA KOTA KENDARI (KAJIAN ETNOLINGUISTIK) - Wulandari, Kiki Reski (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2023)
This study aims to identify about the understanding of tolakinese t-6ribe on the morumbandole marriage tradition, which can be seen from the lexicons they used. The method in this study are ethno linguistic approach as the theoretical and qualitative approach as the methodology. The result ini this study are (1) 19 lexicons included in the mono-morphemes category, (2) 6 lexicons included in the mono-morphemes category, and 11 lexicons included in phrase category